Unequal transition: The widening wealth gap amidst China's rapid growth - Yangtian Jiang; Yu Zheng; Lijun Zhu (Queen Mary University of London, School of Economics and Finance, 2023)
We propose a quantitative theory of wealth creation and distribution during China's transitional growth from the early 1990s, when barriers to setting up private businesses, trading housing, and migrating from rural to urban areas are struck down. In response to the changing economic environment, a small entrepreneurial class emerges and accumulates substantial wealth, whereas the majority working class, partly due to limited investment available from an underdeveloped financial sector, uses housing as the main vehicle of wealth accumulation over the course of a long- time housing boom. Our heterogeneous-agent dynamic equilibrium framework determines growth and equity jointly. We show a reasonably calibrated version of the model matches the rise in urban China's wealth inequality since 1995 almost exactly. We further quantify the relative contribution of different reform measures to the rising inequality and discuss the welfare implications taking into account possible growth-equity trade-offs.
Keywords: E21; O11; O16; O18; 330; Wealth inequality; Capital accumulation; Entrepreneurship; Housing; Migration